Pregnancy outcome in relation to maternal height and weight. - Jha, Rani
ABSTRACT: This study was conducted in the Maternity Hospital, Thapathali. This study has tried to explore the relationship of maternal height and weight with pregnancy outcome in Nepalese context. It has also tried to identify the critical height and weight for Nepalese mothers. The study comprised a group of 360 women fulfilling a certain criteria designed according to the purpose. Besides the maternal height and weight, a detail medical , surgical and obstetric history of the patient was taken. All the patients were subjected to thorough medical examinations like pelvic examination, abdominal examination and respiratory system examination. Nature of labor, mode of delivery and other complications were noted. The weight of fetus, admission in SCBU, morbidity and mortality recorded. Then, these data were subjected to statistical analysis after being transferred to master-chart. The study has identified <_ 144cm height and <_ 50kg weight ad cut-off points among Nepalese mothers. The mothers of<_ 144 cm height had more chances of being <_ 50kg.These mothers had a higher rate of CPD, preterm delivery and LSCS (17.74%). Babies born to such mothers were more asphyxiated at 1 minute of birth and had a higher rate of being LBW babies. They had also a higher of admission to SCBU in comparison to the babies of taller mother (20.96% VS 0.76%). It has been demonstrated through the present study that, maternal height and weight are significantly associated with the mode of delivery and fetal outcome. Short statured mothers are at a higher risk of delivery related complications and therefore, they need the special care.